Procedural Pediatric Sedation by Nurses: Available, Competent, and Safe - Laetiscia Lavoie; Catherine Vezina; Emilie Paul-Savoie; Claude Cyr; Sylvie Lafrenaye (International Journal of Pediatrics)
Sedation and/or analgesia are standard of care for pediatric patients during painful intervention or medical imaging requiring immobility. Physician availability is frequently insufficient to allow for all procedural sedation. A nurse-led sedation program was created at the Centre Hospitalier Universitaire de Sherbrooke (CHUS) to address this problem. Objective. To evaluate the effectiveness and the safety of our program. Methods. A retrospective study of all the procedural sedations done over one year was performed. Complications were separated in four categories: (1) major complications (call for help; unexpected admission, aspiration, and code); (2) reportable sedation events (oxygen saturation <90%, bradycardia (more than 2 SD below normal for the age of the child), and hypotension (more than 2 SD below normal for the age of the child); (3) difficult sedation (agitation, inadequate sedation, and failure to perform the procedure), (4) minor complications. Results. 448 patients, 249 boys and 199 girls; received sedation for 555 procedures. Overall, 78% (432) of interventions were successfully accomplished: 0% of major complications, 8% of reportable sedation events; 5% of difficult sedation; 9% of minor complications. Conclusion. Our nurse-led sedation program compares favorably to other similar systems.